2021
DOI: 10.3390/app11052280
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in the Seismic Assessment of Historical Masonry Buildings

Abstract: Seismic assessments of historical masonry buildings are affected by several sources of epistemic uncertainty. These are mainly the material and the modelling parameters and the displacement capacity of the elements. Additional sources of uncertainty lie in the non-linear connections, such as wall-to-wall and floor-to-wall connections. Latin Hypercube Sampling was performed to create 400 sets of 11 material and modelling parameters. The proposed approach is applied to historical stone masonry buildings with tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…We built upon the existing models by using the ability of the macro-element [38] to explicitly model the out-of-plane behaviour. As shown in Tomić et al [37], when the out-of-plane behaviour is accounted for, the influence of non-linear connections can be highlighted. Therefore, unlike the Tremuri model where the floors were assumed to be perfectly connected to the walls and the stiffness was calibrated accordingly, here we explicitly model the nonlinear connections to base the stiffness of the floor diaphragm on material properties and mechanical formulation.…”
Section: Numerical Modelmentioning
confidence: 92%
See 1 more Smart Citation
“…We built upon the existing models by using the ability of the macro-element [38] to explicitly model the out-of-plane behaviour. As shown in Tomić et al [37], when the out-of-plane behaviour is accounted for, the influence of non-linear connections can be highlighted. Therefore, unlike the Tremuri model where the floors were assumed to be perfectly connected to the walls and the stiffness was calibrated accordingly, here we explicitly model the nonlinear connections to base the stiffness of the floor diaphragm on material properties and mechanical formulation.…”
Section: Numerical Modelmentioning
confidence: 92%
“…A number of such macro-element models have been proposed for unreinforced masonry elements [15,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]; a recent review is included in [14]. The simplicity of this modelling approach allows multiple static and dynamic analyses to be performed in a short time, and a large number of performed analyses can address aleatory and epistemic uncertainties [13,[34][35][36][37]. However, because all but the most recent macro-elements for unreinforced masonry elements [38] capture only the in-plane and not the out-of-plane response, equivalent frame model analyses were restricted to the global response.…”
Section: Introductionmentioning
confidence: 99%
“…Since there were no experimental in situ tests conducted, the uncertainties in the assessment phase were covered by mean values of the material characteristics taken according to the working draft for the new Eurocode EN1998-3 [49]. Uncertainties defined by Tomić et al [50] like the non-linear connections, such as wall-to-wall and floor-to-wall connections were not taken into account. In this document, the mean values of material characteristics are given for different masonry types.…”
Section: Materials Characteristics and Other Input Datamentioning
confidence: 99%
“…In this document, the mean values of material characteristics are given for different masonry types. For solid brick masonry and lime mortar the values are shown in Table 1 [50]. Besides the material characteristics, a few other important factors are used as input data in the software.…”
Section: Materials Characteristics and Other Input Datamentioning
confidence: 99%
“…Bilgin and Ramadani [15] evaluated the structural behavior of historical Bajrakli Mosque located in western of Kosovo using static and dynamic analyses and considering both gravity and lateral seismic loads. Tomic´ et al [16] suggested parametric investigations to assess the seismic behavior of historical masonry buildings that mainly affected by the uncertainty in material properties, construction details and modeling parameters. Usta [17] used three dimensional finite element modeling and fragility analysis to study the seismic performance of historical minarets in Antalya, Turkey.…”
Section: Introductionmentioning
confidence: 99%